Determination of local residual stress in an air plasma spray thermal barrier coating (APS-TBC) by microscale ring coring using a picosecond laser. (1st July 2019) - Zhang, Xun; Li, Chun; Withers, Philip J.; Markocsan, Nicolaie; Xiao, Ping
Abstract: A picosecond laser for incremental annular trench cutting is combined with digital image correlation (DIC) to extend the incremental ring-core method to the profiling of residual stress in thick (>100 μm) coatings. In this case the local residual stress in a TBC is depth profiled after exposure to 1150 °C for 190 h. The topcoat was found to be in compression with an average compressive stress of −94 ± 8 MPa which is representative of the stresses that would be generated elastically on cooling from a stress-free temperature of 970 °C. The stress profile measurements have been validated by high-energy synchrotron X-ray diffraction measurements. Graphical abstract: Unlabelled Image